Genetic context diversity of plasmid-borne blaCTX-M-55 in Escherichia coli isolated from waterfowl. (March 2022) - Zhang, Yanan; Peng, Shan; Xu, Jinge; Li, Yafei; Pu, Ling; Han, Xue; Feng, Yulong
Highlights: IncFⅡ and IncFⅡ-N plasmids may occur through IS26-mediated homologous recombination or conservative transposition, rather than replicative transposition. blaCTX-M-55 were found to be located on IncN, IncFⅡ and IncFII-N fusion type plasmids.Three plasmids shared a homologous region.The homologous region was IS26-ARGs-IS26- bla TEM - orf477-bla CTX-M-55 -▵ISEcp1 -IS26. The clonal spread of bla CTX-M-55- positive strains and horizontal transfer mediated by both conjugative plasmids (IncF, IncN and IncFII-N) carrying transposons (IS26-ARGs-IS26- bla TEM - orf477 - bla CTX-M-55 -ISEcp1△-IS26) contributed to the wide spread of bla CTX-M-55 . ABSTRACT: Objectives: The aim of this study was to explore the prevalence of bla CTX-M and elucidate the characteristics of transferable bla CTX-M-55 plasmids. Methods: Escherichia coli were isolated from 10 large-scale duck farms from nine counties and cities in Guizhou Province. They were identified, subjected to antimicrobial susceptibility testing and screened for antibiotic resistance genes. bla CTX-M -positive strains were subtyped, and bla CTX-M-55 -containing strains were further analysed by multilocus sequence typing, conjugation experiments and polymerase chain reaction–based replicon typing. Three transferable plasmids were selected for whole genome sequencing sequencing and further analysis of genetic context. Results: In total, 128 E. coli strains were identified, and 23 were bla CTX-M -positive. Subtype analysis of bla CTX-M -positive strains revealed that 23 were bla CTX-M-55 and one of the strains contained both bla CTX-M-65 and bla CTX-M-55 . They were divided into 12 multilocus sequence typing types, and 6 were undetermined. bla CTX-M-55 -bearing plasmids in seven were transferred to E. coli C600 at frequencies between 10 −6 and 10 −9, and bla CTX-M-55 was found to be located on IncN, IncFⅡ and IncFII-N fusion type plasmids. Three plasmids (IncFⅡ plasmids pEC99_Plas3 and pS1_Plas2 and IncFII-N plasmid pD2_plas2) shared a homologous region of IS 26 -ARGs-IS 26 - bla TEM - orf477 - bla CTX-M-55 -IS Ecp1 △-IS 26 . Conclusion: Our study demonstrates the environmental presence of bla CTX-M-55 harbouring E. coli in Guizhou. Analysis of the genetic context of bla CTX-M-55 aids in understanding possible dissemination routes of ESBL genes and controlling widespread antibiotic resistance.